Evaluation of long-term effectiveness of modified laparoscopic one-anastomosis gastric bypass in patients with morbid obesity - A. V. Klymenko; V. M. Klymenko; B. S. Kravchenko; K. P. Polishchuk (Zaporožskij Medicinskij Žurnal, 2025)
Aim. To determine the long-term effectiveness of modified laparoscopic one-anastomosis gastric bypass in patients with morbid obesity.